Capacity Building of Library Human Resources through Senayan Library Management System (SLIMs) Training for Digital-Based Collection Processing - Yadi; Alharia Dinata (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2022)
Background: Library is one of the supporting elements in the learning process in the institutions. The circulation of borrowing and returning books is an activity that runs in the library. The process of improving library services can be carried out by officers through various aspects started from the development of collection materials to the dissemination of information. However, in current conditions, there are still many circulation service processes carried out by libraries using conventional media by recording in the library ledger for every user who borrows books. Contribution: The purpose of the activity is to provide knowledge to library managers to be able to take advantage of the Senayan Library Management System (SLiMS) in improving library services. Method: The methodology used is through training and counseling to a librarian. Results: The results of community service activities that have been carried out are the transformation of library processing using digital media in the form of the SLiMS application. Improved services to library users are becoming more optimal. This can be seen in the list of visits increasing to 30% every month and regulations on borrowing books reaching 25%, while delays in returning books have decreased to 2%. This has an impact because the process of tracking book collections is very easy so that the identities of the users are stored and can be monitored by librarian. Conclusion: Services to library members are getting better and the knowledge of library managers is getting optimal in carrying out library processing with the help of SLiMS